Carbohydrate intake affects muscle fatique over two weeks of alpine ski training - Bacharach, D. W.; Bacharach, K. J. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: To help understand how Alpine skiers cope with the stress of multiple weeks of training, this study attempted to maintain hydration levels, monitor carbohydrate (CHO) intake, and force feed some athletes with a carbohydrate-protein (CHO-P) supplement while taking characteristic measurements of fatigue of Alpine skiing over a two week period.